Grizzly 399 : queen of the Tetons [videorecording (DVD)] - Leiter, Elizabeth; Murphy, Bill (Producer); Isler, Jim, 1978-; Nusbaum, Colin; Carter, Daniel (PBS, 2024)
Grizzly 399, the most famous bear in Grand Teton National Park, has an exceptional litter of four cubs to raise. The family must contend with conflicts between people and bears, a warming climate, and human encroachment in bear country.